Kepemimpinan inklusif dan voice behavior pada karyawan: Menguji peran budaya inovatif: Inclusive leadership and voice behavior among employees: Examining the role of an innovative culture - Rohmah, Zakia Nur; Etikariena, Arum; Salendu, Alice (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract Organizational culture is one of the predictors that can influence employees' voice behavior. However, research on organizational innovation culture with employee voice behavior still needs to be more extensive and needed. This study aims to determine the role of innovative organizational culture in mediating the relationship between inclusive leadership and employee voice behavior. The study conveniently sampled 174 employees from various innovative companies. The measuring instruments used are the Inclusive Leadership Scale (α = 0.85), Organizational Culture Assessment Instrument (α = 0.84), and the Voice Behavior Scale (α = 0.93) which have been adapted into Indonesian—data analysis with the PROCESS 4 model from Hayes. The result highlights that inclusive leadership was positively correlated with employee voice behavior, and innovative culture partially mediated the relationship between inclusive leadership and employee voice behavior. The implication for organizations is to set up leaders with inclusive characteristics through self-development and training, facilitating safe environments to express employee voices and opinions by implementing values that support flexibility and autonomy. Keywords: Innovative culture; Inclusive leadership; Voice behavior; Organizational culture Abstrak Budaya organisasi merupakan prediktor yang mampu memengaruhi perilaku bersuara bagi karyawan. Namun, penelitian terkait budaya inovatif organisasi bersama dengan outcome perilaku bersuara karyawan ini masih minim diteliti dan memerlukan eksplorasi lebih lanjut. Penelitian ini bertujuan mengetahui peranan budaya inovatif organisasi dalam memediasi hubungan antara kepemimpinan inklusif dan perilaku bersuara karyawan. Sampel penelitian adalah karyawan yang bekerja dari beberapa perusahaan yang diprediksi memiliki budaya organisasi yang inovatif dengan jumlah populasi yang tidak diketahui secara pasti dan dipilih menggunakan teknik convenience sampling. Alat ukur yang dipakai adalah Inclusive Leadership Scale (α = 0.85), Organizational Culture Assessment Instrument (α = 0.84), Voice Behavior Scale (α = 0.93) yang telah diadaptasi ke dalam Bahasa Indonesia. Analisis data dengan PROCESS model 4 Hayes. Hasil menunjukkan bahwa kepemimpinan inklusif secara positif berkorelasi dengan voice behavior, budaya inovatif memiliki efek mediasi parsial pada hubungan kepemimpinan inklusif dan voice behavior karyawan. Implikasi penelitian ini bagi organisasi supaya mampu memfasilitasi lingkungan yang aman bagi karyawan dalam menyampaikan suara dan pendapatnya dengan menyiapkan pemimpin-pemimpin yang memiliki karakteristik inklusif melalui pengembangan diri dan training serta menerapkan nilai-nilai yang mendukung fleksibilitas dan otonomi bagi karyawan. Kata kunci: Budaya inovatif; Kepemimpinan inklusif; Perilaku suara; Budaya organisasi